Impact of local environmental standards on water environmental carrying capacity in large water diversion project: A system dynamics analysis in Shandong, China. (15th August 2022) - Bing, Liu; Haojun, Xi; Yeting, Hu; Zhe, Liu; Tianhong, Li; Zhuqing, Wen
Abstract: Large water diversion projects have extensive impact on the water systems in the receiving areas, where inevitable regional responses are aroused and alert to local environmental carrying capacity. To ensure the water quality of China's eastern South-to-North Water Diversion Project (SNWDP), Shandong Province had issued strict local wastewater discharge standards since 2006. However, some flexibility exists in the enforcement of local standards, which created uncertainty to the outcomes. A system dynamic (SD) model and Water Environmental Carrying Capacity (WECC) method were integrated to dynamically illustrate the interaction between the enforcement of the local standards and the performance of the regional water system. The WECC was calculated based on an indicator system representing the multi-dimensional impact of the local standards on the regional water system. The SD model was constructed to simulate and forecast the variations of those indicators of WECC. The SD-WECC model was trained and validated with yearly data from 2000 to 2020, then four scenarios with different levels of enforcement of local standards were illustrated. The results showed that overall WECC improves during period from 2000 to 2025, and that the SNWDP improves the balance of water supply and demand in Shandong in the long run in the three scenarios that have introduced the local standards. The adoption of the local standard helps the concentration of industrial Chemical Oxygen Demand (COD) discharge to meet the discharging standards earlier by stimulating the investment in pollution control. Therefore, the flexibility in local water environment management enabled the local actors to pursue a balance between environmental protection and economic growth in a dynamic context with multi-objects for local development.